The impact of regional and demographic factors on the efficiency of German savings banks - Alexander Conrad; Doris Neuberger; Lucinda Trigo Gamarra (Universität Rostock, Institut für Volkswirtschaftslehre, 2009)
This paper examines the influence of environmental factors on technical, cost, scale and revenue efficiency of German savings banks in 2001-2005. Taking into account growing regional disparities in economic wealth and population size, it differentiates between declining and growing regions. Regional and demographic factors explain part of the variation in efficiency levels. Population density and branch penetration positively affect efficiency in growing regions. A negative impact of economic power and a positive impact of competitive pressure on efficiency support the quiet life hypothesis. In declining regions, a larger share of elder people reduces bank efficiency. Savings banks seem to be well adapted to unfavorable environmental conditions.
Keywords: G21; D21; D24; R1; 330; savings banks; efficiency; Data Envelopment Analysis; demographic change; regional disparities; Sparkasse; Wirtschaftliche Effizienz; Regionale Entwicklung; Regionale Bevölkerungsentwicklung; Schätzung